Laparoscopic anterior resection for rectal stenosis caused by ALTA injection for internal hemorrhoids: A case report. Issue 2 (12th August 2020) - Yoshimitsu, Masanori; Egi, Hiroyuki; Kaneko, Mayumi; Shimomura, Manabu; Hakoda, Keishi; Miguchi, Masashi; Kohashi, Toshihiko; Hihara, Jun; Hirabayashi, Naoki; Ohdan, Hideki
Abstract: We herein report the first case of rectal stenosis that developed after internal hemorrhoid treatment with aluminum potassium sulfate and tannic acid (ALTA) therapy that was successfully treated by laparoscopic surgery. A 72‐year‐old man suffered from a fever and rectal stenosis after undergoing internal hemorrhoid treatment with a submucosal injection of ALTA at a previous clinic. Three months after ALTA therapy, he developed frequent mucous and bloody stools. Lower intestinal tract endoscopy revealed circumferential severe rectal stenosis. He was therefore referred to our hospital. The patient suffered from frequent stool build‐up and difficulty defecating. We performed balloon‐dilatation intervention. The stenosis was not improved at all. Five months after ALTA therapy, we performed laparoscopic low anterior resection with diverting ileostomy. Three months after the operation, ileostomy takedown was performed. The patient has experienced no rectal stenosis in the 2 years since his radical operation.